The Effect of Appreciative Inquiry as OD Intervention on Planning and Service Quality Improvement - Chandramouli More, Bro. (SFIMAR Research Review, 2012)
In general schools are used to annual planning models in spite of its weaknesses (process) and limitations (perspective). The focal organization based in a metro in India is no exception. In a significant departure from this general trend, this action research intends to craft a three-year holistic development plan for a school organization by employing an all-inclusive approach called Appreciative Inquiry. Further, the study examines the effect of Organizational Development Intervention (ODI) on the organization’s service quality. The study combines both qualitative and quantitative methods for data collection and analysis. In addition to formulating the development plan, the study finds significant difference between Pre and Post ODI in terms of parents’ satisfaction toward service quality in three out of the six dimensions.